The Concept of Competitiveness of Small and Medium-Sized Enterprises In Poland in Times of Extraordinary Threat - Magdalena MAJCHRZAK (Communications of International Proceedings, 2021)
Competitiveness is a category appreciated by economic theorists and practitioners. In the microeconomic scale, competitiveness relates mainly to enterprises which, in order to be successful on the market, must have an appropriate competitive position. Obtaining such a position is possible thanks to having the advantages appreciated by the market. These advantages are divided along the value chain composed of the basic functions of the enterprise, and obtaining a competitive advantage depends on the results achieved in the individual links of the chain. Obtaining dominance in at least one of the analyzed chain links enables the company to achieve a decisive advantage. The aim of the article is to create a concept of the competitiveness of small and medium-sized enterprises in Poland in times of extraordinary threat. The research hypothesis was formulated as follows: the factors of enterprises' competitiveness change over time and require constant monitoring in order to maintain the competitiveness of enterprises. Verification of the hypothesis and implementation of the goal will be carried out thanks to theoretical and empirical research of small and medium-sized enterprises in Poland.
Keywords: competitiveness; small and medium-sized enterprises; extraordinary threat